2016
DOI: 10.1371/journal.pgen.1006510
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Fibroblast Growth Factor Signaling Is Critical for the Pathogenesis of the Dwarfism in Evc2/Limbin Mutant Mice

Abstract: Ellis-van Creveld (EvC) syndrome is a skeletal dysplasia, characterized by short limbs, postaxial polydactyly, and dental abnormalities. EvC syndrome is also categorized as a ciliopathy because of ciliary localization of proteins encoded by the two causative genes, EVC and EVC2 (aka LIMBIN). While recent studies demonstrated important roles for EVC/EVC2 in Hedgehog signaling, there is still little known about the pathophysiological mechanisms underlying the skeletal dysplasia features of EvC patients, and in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Treatment of primary chondrocytes with PTH(1-34) suppressed expression of Fgfr3 (Zhang et al, 2016) as did injection of PTH(1-34) in vivo (Karuppaiah et al, 2016). Although not investigated in chondrocytes, Fgfr3 expression was induced by hypoxia in a transcriptional and HIF1α-dependent manner in bladder cancer cells (Blick et al, 2013).…”
Section: Regulation Of Fgfr3 Expressionmentioning
confidence: 99%
“…Treatment of primary chondrocytes with PTH(1-34) suppressed expression of Fgfr3 (Zhang et al, 2016) as did injection of PTH(1-34) in vivo (Karuppaiah et al, 2016). Although not investigated in chondrocytes, Fgfr3 expression was induced by hypoxia in a transcriptional and HIF1α-dependent manner in bladder cancer cells (Blick et al, 2013).…”
Section: Regulation Of Fgfr3 Expressionmentioning
confidence: 99%
“…In this study, we found loss of function of Evc2 results in premature closure of the ISS before P8 in Evc2 global mutants and in Evc2 Wnt1 mutants. We previously reported that loss of function of Evc2 results in severe chondrodysplastic dwarfism; however, we never observed premature closure of appendicular growth plates through adult stages ( Zhang et al, 2016a ). Those data suggest that a function of Evc2 to maintain cartilage is different between appendicular growth plates and synchondroses.…”
Section: Discussionmentioning
confidence: 49%
“…We and others have used both Evc and Evc2 mutant mice to characterize different aspects of abnormal development ( Ruiz-Perez et al, 2007 ; Caparros-Martin et al, 2013 ; Zhang et al, 2015 ). Generating our own Evc2 mutant mice enabled us to characterize the pathological mechanisms leading to abnormal appendicular bone and hypomorphic enamel development ( Zhang et al, 2015 , 2016a , b ). Our subsequent studies further demonstrated the expression of Evc2 in the mid-facial regions ( Badri et al, 2016a ) and mid-facial defects in Evc2 global mutant mice ( Badri et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…This is further supported by comparisons of mRNA levels of Gli1 and Ptch1 between multiple tissues between control and Evc or Evc2/Limbin mutant mice [ 10 , 25 ]. As pointed out by Zhang et al [ 25 ], the partially compromised, instead of largely attenuated, Hedgehog signaling is the likely reason leading to normal lips, palate and neural tube development in humans affected by EVC and in Evc or Evc2/Limbin mutant mice [ 9 , 10 , 25 ], as summarized in Table 1 . On the other hand, simply believing that the partially compromised Hedgehog signaling is the reason leading to the abnormal phenotypes in mutant mice or signs in humans may lead to an inaccurate understanding of the pathological mechanism.…”
Section: Primary Cilium Ciliopathy and Evcmentioning
confidence: 85%
“…It should be noted that multiple lines of evidence suggest that EVC or EVC2/LIMBIN loss of function only partially compromises Hedgehog signaling [ 9 , 11 , 25 ]. This critical detail is supported by both in vitro molecular studies and in vivo phenotypic studies.…”
Section: Primary Cilium Ciliopathy and Evcmentioning
confidence: 99%